Pengembangan Modul Berbasis Model Pembelajaran Problem Solving Pada Tema 9 Subtema 1 Benda Tunggal dan Campuran Kelas V SD/MI - Sundahry (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research was conducted with the aim of (1) producing teaching materials in the form of modules using problem solving learning models for the thematic subjects for class V SD/MI (2) Knowing student responses to modules using problem solving learning models in thematic learning for class V SD/MI. This type of research is Research and Development (R&D) based on the modifications developed by Sugiyono. The stages in this study were carried out from stage 1 to stage 7, namely potential and problems, data collection, product design, product validation, product design revision, product testing, product revision. Module Development Based on Problem Solving Learning Model on Theme 9 Sub-theme of the Singular and Mixed Class V SD/MI by using the Research and Development model Borg and Gall modified by Sugiyono which includes stages of potential and problems, collecting data, product design, design validation, design revision, product trials, and product revisions. Student responses to the Problem Solving Learning Model-Based Module on Theme 6 Sub-theme of the Human Body Class V SD/MI obtained an average score of 3.28 with very interesting criteria. The educator's response to the Problem Solving Learning Model-Based Module in Theme 6 Sub-theme of the Human Body Class V SD/MI obtained an average score of 3.32 with very interesting criteria. It can be concluded that the module based on the problem solving learning model of the thematic learning of the fifth grade human body sub-theme that was developed is feasible to be used as teaching material.